Anatomical examination of Iranian endemic Stachys acerosa Boiss. (Lamiaceae): implications for the separation of morphologically similar species (Bangladesh Journal of Botany, 2022)
An anatomical study was conducted in Stachys acerosa Boiss. is endemic to Zagros Chain Mountains in Iran. In the current study the samples were collected from Oshtorankuh Mountain and examined. Vegetative and reproductive organs anatomically using light microscope. The distinguishing feature of S. acerosa is the presence of sclerenchyma at the angles of the stem. Five types of trichomes - simple nonglandular uniseriate uni- and multicellular, short and long capitate glandular, and glandular peltate trichomes were found on the surface of vegetative and reproductive organs. The leaves are amphistomatic and isobilateral; and the mesophyll is composed of four-layers palisade parenchyma. Two of them present at the upper side and another two layers at lower side and in between palisade layers two-layered spongy parenchyma were existed. The present study shows that the certain anatomical features of Stachys taxa are valuable for species delimitation.Bangladesh J. Bot. 51(2): 325-334, 2022 (June)